Altered lectin-binding sites in normal colon and ulcerative colitis - Mario R. Melo-Júnior; Adriana M. S. Telles; Francisco E. B. Albuquerque; Nicodemos T. Pontes-Filho; Luiz B. Carvalho Jr; Eduardo I. C. Beltrão (Sociedade Brasileira de Patologia Clínica, 2004)
The aim of this study was to evaluate the expression of carbohydrates via lectin histochemistry and computer image analysis in normal colon and ulcerative colitis. Sections of human intestinal tissues (4mm) were incubated with lectins (Con A, WGA, LTA and PNA) and evaluated through optical microscopy. Staining results were analysed using an image analysis programme. The results showed a positive intense staining pattern to the inflammatory cells, mainly neutrophils of sigmoid and rectum portion of colon as well as epithelial gland cells. WGA and LTA lectins showed distinct patterns between normal gland epithelium and ulcerative colitis. PNA and Con A failed to recognize carbohydrate moieties in studied cases. The results were also confirmed by the image analysis. The observations reported here suggest that WGA and LTA lectins are promising histologic markers to differentiate normal gland epithelium from inflammatory ulcerative colitis regarding the differences observed in the expression of N-acetylglucosamine and L-fucose.